Lietuvių kalbos veiksmažodžių atvirųjų šaknų problema - Kruopienė, Irena (Kalbotyra, 1998)
The article deals with the problem of open roots, which formally end with vowels. Such roots can only be found in the stem of the infinitive, but the consonants [j] and [v] can be found in other forms of the verb, e.g. lóti -lója, lójo “to bark”; sė́ti - sė́ja, sė́jo “to sow”; žū́ti - žū̃va, žùvo “to die”; kliáuti - kliáuja, klióvė “to trust”. Considering the phonological structure of the root, the sounds [j] and [v] should be interpreted not as interfixes (connectors), but as parts of the root, which may be the way to solve the problem of unusual open roots of verbs in Lithuanian.